The impact of working from home during the COVID-19 pandemic on the wellbeing of office workers in the UK: A qualitative analysis. - Guest, Emma (2020)
The COVID-19 pandemic has resulted in people all over the world being forced to work from home. Working from home (WFH) has various consequences, both positive and negative, for individuals, organisations and society. The impact it can have on wellbeing has received attention in the literature, given that employee wellbeing has increasingly become an issue for organisations. The COVID-19 pandemic is also undoubtedly affecting the wellbeing of individuals. This study adopts a qualitative approach to examine how WFH during the COVID-19 pandemic has affected the wellbeing of office workers in the UK. Semi-structured interviews were carried out with office workers who had been WFH during the COVID-19 pandemic. The results of this study show that wellbeing has been both positively and negatively affected by WFH in three main ways; an improvement in work-life balance (WLB), a deterioration in WLB, and through feelings of social isolation. The restrictions imposed due to the COVID-19 pandemic appeared to intensify these consequences and age appeared to be a moderating factor as well. Office workers agree that WFH will become more common within our society, with a mixture of WFH and working in an office being the most preferable working arrangement. This study highlights the importance of organisations supporting employee wellbeing and listening to employee needs, as they continue to work from home and their wellbeing continues to be affected.